2020
DOI: 10.1002/fsn3.1520
|View full text |Cite
|
Sign up to set email alerts
|

Fruit‐based drink sensory, physicochemical, and antioxidant properties in the Amazon region: Murici (Byrsonima crassifolia (L.) Kunth and verbascifolia (L.) DC) and tapereba (Spondia mombin)

Abstract: Increased fruit consumption due its protective effect on the organism is accompanied by the development of the processing industry of these products. The aim of this work was to optimize fruit pulp‐based beverage formulations from the murici and tapereba Amazon region, taking into account their sensory acceptance and antioxidant activity. Total soluble solid content, reducing sugar content, titratable acidity contents, pH, and ascorbic acid content were determined in pulps and formulations. The total content p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…A study observed, for the ORAC assay, that murici presented an amount of 3352.3 ± 952.0 μmol TE/100 g [ 4 ]. The potent antioxidant activity of murici and taperebá fruit pulp may be associated with their content of vitamin C and phenolic compounds, as well as with the occurrence of carotenoids in their composition [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study observed, for the ORAC assay, that murici presented an amount of 3352.3 ± 952.0 μmol TE/100 g [ 4 ]. The potent antioxidant activity of murici and taperebá fruit pulp may be associated with their content of vitamin C and phenolic compounds, as well as with the occurrence of carotenoids in their composition [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activities of the 30%, 60%, and 95% ethanol extracts of R. himalense fruits were determined microassay, using the T‐AOC assay (DPPH, ABTS, and FRAP) kits purchased from Suzhou Comin Biotechnology Co., Ltd. (Jiangsu, China). The scavenging capability for DPPH free radical and ABTS radical cation (ABTSˑ + ) was evaluated by applying a microplate reader in absorbance at 515 and 734 nm, respectively (Abreu et al., 2019; Arts et al., 2004; Souza et al., 2020). The results of DPPH and ABTS were expressed as trolox equivalent antioxidant capacity (TEAC), which is µmol TEAC/g fresh weight and determined via a calibration curve, such as y = 0.7072x − 0.0081, R 2 = 0.9977 and y = 0.7021x − 0.0012, R 2 = 0.9985.…”
Section: Methodsmentioning
confidence: 99%
“…The fermented alcohol of B. crassifolia was classified as a semidry table wine. Fruit-based beverage formulations with B. crassifolia and Spondias mombin L. (cajá) were well-accepted and presented antioxidant properties (Souza et al 2020).…”
Section: Other Species With Technological Potentialmentioning
confidence: 99%